Synthesis of W-Doped TiO2 Material Ratio Using One-Step Solvothermal Method and Treatment Orientation of Volatile Organic Compounds - Chau, Hung Dung; Tuu, Tran Thi; Sy, Phung Chi; Tan, Lam Van; Tran, Thi Kim Ngan (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
In TiO2 photocatalysts have been interested in the world thanks to many advantages in handling toxic compounds, with great potential for practical application at low cost. However, the electron-hole recombination rate is still high and can not be processed under visible light, which is a major limitation of this material. Modification of TiO2 by W6+ is a possible solution, however there is still little research and the optimal W6+ ratio in small amounts is still low. The material was synthesized by a one-stage solvothermal method at 200 ºC for 10 hours, without using any surfactants or post-reaction calcination with doped W molar ratios of 0.5%, 1%, and 1.5%. The result was that the TiW-1.5% catalyst sample had the highest specific surface area of 175 m2/g, higher than pure TiO2 of 160.0 m2/g. The W6+ ion successfully replaced Ti4+ in the TiO2 crystal lattice, reducing the band gap energy of the catalytic sample to 2.88 eV with the TiW-1.5% sample. For TiW-0%, the formaldehyde decomposition ability is 53.50%. Doping W into TiO2 increased catalytic efficiency, with a material sample with an optimal modified W content of 1.5% mol W having a formaldehyde decomposition efficiency of 71.98%. Research results show that W modification can improve the activity of TiO2 and increase the efficiency of volatile organic compound treatment. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).